Conservation of bamboo species in a mini urban ecosystem of Bangladesh - Rahman, MM; Parvin, W; Sultana, N; Tarek, SAM (Journal of Biodiversity Conservation and Bioresource Management, 2018)
A bambusetum conserving all bamboo species of Bangladesh was established at Bangladesh Forest Research Institute campus, Chittagong. The Silviculture Genetics Division conducted the research study. The purpose of the study was to collect, centralize and conserved all bamboo species of Bangladesh in a setum. The planted propagules of various species include offsets, part-clump, branch cutting, seed and seedling and tissue culture plantlets. So far 33 species of bamboos have been collected from different parts of the country as well as introduced from China and Thailand. The total land area of the bambusetum is approximately 2.0 hectares. It is the only bamboo germplasm centre of the country, which includes all bamboo species. It serves as a bamboo information center for the scientists, academicians, students and visitors as well. J. Biodivers. Conserv. Bioresour. Manag. 2017, 3(2): 35-42